PROFESSIONAL TRAINING OF JUDICIAL INTERPRETERS IN SUB-SAHARAN AFRICA, THE CASE OF GHANA - (:unkn) unknown (My University, 2022)
AbstractIn a world of many spoken languages, interpretation certainly becomes an indispensable tool to break the spoken language barriers. Many countries and regions almost across the world have made advances to various positions in standardizing T&I. Given the dire consequence of defective interpretations especially in sensitive places like the courts, hospitals, churches etc, quality interpretation should not be sacrificed on the altar of necessity. This article set out to explore the situation of professional training for court interpreters in sub- Saharan Africa, using Ghana as a case study. Questionnaires and unstructured interviews for court administrators and practicing interpreters as well as tapping conversations and their respective interpretations in the courts yielded rich data for analysis. Valdeón’s Selective Appropriation (2008) was especially used to assess the quality of interpretation in the courts. The responses were analysed in five thematic areas and revealed that though interpretation is valued, T&I are not regulated, there are no professional interpreters and there are very limited if any, professional institutes for training interpreters. There is no legislation nor a professional body among others to help sanitize T&I.
Keywords: African Research